Montierte Texte, hybride Helden : zur Poetik der Wolfdietrich-Dichtungen - Miklautsch, Lydia (Quellen und Forschungen zur Literatur- und Kulturgeschichte ;, 2005)
Considered by researchers to be typical post-classical adaptations of medieval narratives and of lesser literary value, the poems about the Germanic hero Wolfdietrich are among the?best sellers? of the Late Middle Ages. The author investigates the reason.